The story of Jesus and the blind man: a speech act reading of John 9 - Hisayasu Ito (Acta Theologica)
From text: Since the enigmatic nature of John’s Gospel has attracted a great deal of attention from many scholars, numerous studies of this Gospel have been produced. Each endeavour to understand the Gospel demonstrates its own uniqueness, and utilises one of various methodological approaches to suit its particular research purpose. Methodologically, however, modern critical  research on this Gospel can be roughly divided into two categories, namely historical approaches and literary approaches, which some scholars further divide into ideological (theological) approaches.